Changes in children's food group intake from age 3 to 7 years: comparison of a FFQ with an online food record. Issue 2 (28th July 2014) - Vereecken, Carine; Covents, Marc; Huybrechts, Inge; Kelly, Colette; Maes, Lea
<x content-type="archive" xml:space="preserve">Abstract</x> Few studies have investigated the relative validity of FFQ in young children and no study has investigated the relative validity of changes in children's food intake in a longitudinal context. The aim of the present study was to compare the FFQ of the longitudinal Family Influences on Food Intake study, assessing children's food intake in the previous 3 months, with a 3 d online food record when children were 3 and 7 years old, as well as to investigate the relative validity of changes in food group intake over a 4-year period. Parents (n 89) completed the FFQ and an online food record over three non-consecutive days on two separate occasions (January–April 2008 and 2012). Wilcoxon signed-rank tests and Spearman's correlations were used to compare food group intake and changes in intake assessed using both methods. In 2008, the intake of eleven of the twenty-two food groups was overestimated and that of four food groups underestimated in the FFQ in comparison with the online tool; in 2012, the intake of four food groups was overestimated and that of seven food groups underestimated. Nevertheless, changes in intake did not differ significantly between the two methods for eighteen food groups. Correlations in 2008 and 2012 were, on average, 0·47; correlations between the changes in dietary intake were, on average, 0·26. The results suggest that despite the significant differences between the two methods for a number of food groups at both baseline and/or follow-up, the FFQ can be used to monitor changes in dietary intake for groups of young children.